Respuesta :

Answer:

A(-7 , -13) → A(-13, -7) →A''(7, -13)

B(12, -8)   → B'(-8, 12) →B''(-12, -8)

C(-17, 19) → C'(19, 17)  →C''(-17, 19)

Step-by-step explanation:

A(-7 , -13), B(12, -8), C(-17, 19)

The rule (x,y) reflection across the line y = xis (x,y)  → (y, x)

A(-7 , -13) → A(-13, -7)

B(12, -8)   → B'(-8, 12)

C(-17, 19) → C'(19, 17)

The rule for a rotation by 90° about the origin is (x,y) → (-y,x)

A(-7 , -13) → A(-13, -7) →A''(7, -13)

B(12, -8)   → B'(-8, 12) →B''(-12, -8)

C(-17, 19) → C'(19, 17)  →C''(-17, 19)

ACCESS MORE